Integrating Civic Philanthropy and Civic Responsibility to Strengthen Community-Based Waste Bank Management in Kampung Pasir, Garut Regency - Pat Kurniati; Asep Anggi Dikarsa; Nabil Jawad Dhiya’ul Haq; Fitri Aliyya Lestari (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to strengthen environmental awareness and community participation through the integration of civic philanthropy and civic responsibility in the implementation of a waste bank program in Kampung Pasir, Cintakarya Village, Garut Regency, Indonesia. The program was implemented in collaboration with the indigenous community of Kampung Pasir using a participatory community empowerment approach over a six-month period. The activities included environmental awareness campaigns, technical training on waste management, the establishment of a waste bank management committee, and continuous mentoring to support program implementation and sustainability. The program was evaluated using a post-test questionnaire administered to 45 participants, complemented by observations, interviews, and documentation. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed using descriptive qualitative analysis. The evaluation results showed an overall achievement score of 82.72% (mean = 3.31 on a 4-point scale), indicating a good level of program effectiveness. The achievement scores for each evaluation dimension were 83.89% for environmental knowledge, 85.56% for civic responsibility, 80.00% for behavioral change, and 81.44% for civic philanthropy, all of which were categorized as good. Furthermore, during the six-month implementation period, approximately 400 kg of economically valuable inorganic waste was collected, eight waste bank committee members were formally appointed, and regular mentoring sessions were conducted to strengthen the program's institutional sustainability. These findings demonstrate that integrating civic philanthropy and civic responsibility into community-based waste bank programs can effectively strengthen community-based waste management, enhance environmental awareness and community participation, and support the long-term institutional sustainability of waste banks within indigenous communities.